S109 Genome-wide analysis of longitudinal lung function and gas transfer in individuals with idiopathic pulmonary fibrosis. (11th November 2022) - Allen, RJ; Oldham, JM; Jenkins, DA; Leavy, OC; Guillen-Guio, B; Melbourne, CA; Ma, SF; Jou, J; Kim, JS; Fahy, WA; Oballa, E; Hubbard, RB; et al.
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is a progressive disease where the lungs become progressively scarred, reducing lung capacity and impairing gas transfer. Genome-wide association studies (GWAS) have identified a number of genetic loci associated with risk of IPF. Aim: To identify genetic loci associated with declining lung capacity or declining gas transfer. Methods: We performed a GWAS of longitudinal measures of forced vital capacity (FVC, a measure of lung capacity) and diffusing capacity for lung of carbon monoxide (DLco, a measure of gas transfer) using a linear mixed effects model. This was performed in individuals diagnosed with IPF across three studies and identified variants for further follow-up in an additional independent study. Variants were defined as significantly associated if they had p<5×10 −8 in a meta-analysis of all four studies, had consistent direction of effects across and were nominally significant (p<0.05) in each study. Results: 1, 048 individuals with measures of longitudinal FVC and 729 individuals with longitudinal measures of DLco passed quality control. In total, 4, 560 measures of FVC and 2, 795 measures of DLco and over 7 million genetic variants were included in the analysis. One variant located in an antisense RNA gene for Protein Kinase N2 ( PKN2 ) showed a genome-wide significant association with FVC decline (−140 ml/year per risk allele, 95% CI [−180, −100], p=9.14×10 −12 ) with consistent effects across all four studies. Conclusion: These results identify a possible druggable target involved in promoting IPF disease progression. Please refer to page A211 for declarations of interest related to this abstract.